2021
DOI: 10.3390/cells10113090
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1, GLUT3 Expression and 18FDG-PET/CT in Human Malignant Melanoma: What Relationship Exists? New Insights and Perspectives

Abstract: Background: Malignant melanoma is the most aggressive of skin cancers and the 19th most common cancer worldwide, with an estimated age-standardized incidence rate of 2.8–3.1 per 100,000; although there have been clear advances in therapeutic treatment, the prognosis of MM patients with Breslow thickness greater than 1 mm is still quite poor today. The study of how melanoma cells manage to survive and proliferate by consuming glucose has been partially addressed in the literature, but some rather interesting re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Glut-1 is frequently found over-expressed in tumor cell membranes, including melanomas [ 31 ]. How melanoma cells manage to survive and proliferate by consuming glucose has been partially addressed in the literature, but some rather interesting results have been presented [ 50 ]. Different studies have demonstrated an Important connection between PI3K activity and membrane translocation of Gluts [ 21 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glut-1 is frequently found over-expressed in tumor cell membranes, including melanomas [ 31 ]. How melanoma cells manage to survive and proliferate by consuming glucose has been partially addressed in the literature, but some rather interesting results have been presented [ 50 ]. Different studies have demonstrated an Important connection between PI3K activity and membrane translocation of Gluts [ 21 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…P53 can inhibit GLUT1 expression in cells, resulting in decreased glucose uptake and thus inhibiting tumor development ( Feng et al, 2018 ). GLUT3 is expressed in most cancer cells but rarely in normal cells, facilitating glucose consumption ( Cazzato et al, 2021 ; Libby et al, 2021 ). Targeting GLUT can inhibit the degree of aerobic glycolysis, affecting tumorigenesis ( Fu et al, 2021 ; Kim E et al, 2021 ).…”
Section: Glucose Metabolism In Neoplastic Cellsmentioning
confidence: 99%